Analyze the Interactive Biography System of the President of Indonesia: Portfolio - Yudha Nurfaiz; Khilma Zulfani Shobiyyah; Risha Febrianti; Dzaky Raihan Muharram (Academic Bright Collaboration, 2025)
Interactive biography systems have become an important tool in introducing and understanding important figures in history. This article aims to analyze and describe an interactive biography system that focuses on Indonesian presidents. By utilizing various media, including text and images, the system offers an immersive learning experience and interacts with information about Indonesian leaders. Our analysis covers content structure, user interface, and interactivity, as well as their impact on people's understanding of history and leadership. By exploring the various features and technologies used in this system, this article provides an in-depth insight into how information technology can enrich historical learning and promote a better understanding of the role of leaders in the formation of the country. The conclusions of this analysis can provide valuable guidance for the development and improvement of future interactive biography systems.